Microbial Colonization From the Fetus to Early Childhood—A Comprehensive Review - Senn, Viola; Bassler, Dirk; Choudhury, Rashikh; Scholkmann, Felix; Righini-Grunder, Franziska; Vuille-dit-Bille, Raphael N.; Restin, Tanja (Frontiers in Cellular and Infection Microbiology, 2020)
The development of the neonatal gastrointestinal tract microbiota remains a poorly understood process. The interplay between neonatal (gestational age, genetic background), maternal (mode of delivery, nutritional status) and environmental factors (antibiotic exposure, available nutrition) are thought to influence microbial colonization, however, the exact mechanisms are unclear. Derangements in this process likely contribute to various gastrointestinal diseases including necrotizing enterocolitis and inflammatory bowel disease. As such, enhanced understanding of microbiota development may hold the key to significantly reduce the burden of gastrointestinal disease in the pediatric population. The most debatable topics during microbial seeding and possible future treatment approaches will be highlighted in this review.